Analysis of Serum Electrolytes Variation in Onset and Progression of Preeclampsia : Serum Electrolytes Variation in Preeclampsia - Mumtaz, Tamseela; Shahid, Sania; Mustafa, Nageen (Pakistan Journal of Health Sciences, 2023)
Preeclampsia is one of the most common, life-threatening complications of pregnancy that is related to maternal as well as perinatal morbidity or mortality. One of the significant causes of preeclampsia is elevated blood pressure which is directly linked with concentrations of electrolytes in the blood. Objective: To evaluate the possible variations of electrolytes in preeclamptic pregnant females. Methods: A total of 90 pregnant females of 20 to 45 years of age were divided into three groups (n=30 in each group) viz normotensive, hypertensive, and preeclamptic pregnant females. All anthropometric and biophysical variables were measured. Among biochemical parameters, serum sodium, potassium, chloride, and calcium levels were determined using colorimetric assays while bicarbonate levels were determined by an enzymatic test using phosphoenolpyruvate carboxylase and a stable nicotinamide dihydrogen phosphate analogue. A comparison of serum electrolytes among different groups was executed by one-way analysis of variance. Results: Preeclamptic females had significantly higher BMI, and systolic and diastolic blood pressure than hypertensive and normotensive pregnant females (p<0.0001). Serum concentrations of sodium and calcium were significantly lower in preeclamptic pregnant females compared to hypertensive pregnant and normotensive pregnant females (p<0.0001). Conclusions: Alteration in the electrolyte levels may contribute to the onset and progression of preeclampsia. Nutritional sodium restriction along with adjuvant supplementation of Ca⁺⁺, Na⁺, K⁺, and Clˉ may minimize the risk of preeclampsia. On the basis of outcomes, it is recommended that pregnant females should eat a balanced diet that contains appropriate amounts of minerals micronutrients, and vitamins.